The Experimental Study on Concrete Permeability of Wireless Communication Module Embedded in Reinforced Concrete Structures. (18th June 2013) - Jo, Byung-Wan; Park, Jung-Hoon; Yoon, Kwang-Won
Abstract : Recently, as the information industry and mobile communication technology develop, their study is conducted on the new concept of intelligent structures and maintenance techniques that apply wireless sensor network, USN (Ubiquitous Sensor Network), to social infrastructures such as civil and architectural structures on the basis of the concept of Ubiquitous Computing, which invisibly provides human life with computing, along with mutually cooperating, compromising, and connecting networks to each other by having computers within all objects around us. The purpose of this study is to investigate the capability of wireless communication of sensor node embedded in reinforced concrete structure with a basic experiment on electric wave permeability of sensor node by fabricating molding with variables of concrete thickness and steel bars that are mostly used in constructing structures to determine the feasibility of application to constructing structures with USN. By installing wireless communication module inside the structures, it is possible to communicate to measure the pitch of steel bars and permeability of concrete, by measuring in both directions horizontally and vertically. The magnitude of an electric wave in the range of used frequencies was measured by using Spectrum Analyzer. This electric wave was numerically analyzed and the effective wavelength of frequencies was analyzed by the properties of a frequency band area. As a result of constructing structures with wireless sensors, Plain concrete showed 45 cm for depth of permeability. Reinforced concretes that has pitches of 5 cm showed 37 cm and pitches of 15 cm showed 45 cm for the depth of permeability. This suggests that if the pitch of steel bars was more than 15 cm, it would not affect wireless communication.